KENDALA PEMERINTAH DALAM KEGIATAN PELESTARIAN MANGROVE SEBAGAI SARANA PENGURANGAN RESIKO BENCANA DI KOTA PARIAMAN - Nadia Arfa Pratiwi; Zikri Alhadi (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
The erticel is intends to determine the constraints and obstacles of the government in preserving mangroves as a means of disaster risk reduction in Kota Pariaman, mangroves have many benefits for the community, especially in disaster risk reduction in Kota Pariaman, but there are obstacles faced by the government in terms of mangrove conservation activities in the City. Pariaman, mangroves that grow around the coast in Kota Pariaman have been damaged by irresponsible persons, resulting in a reduction in mangrove forest land in Kota Pariaman even though Kota Pariaman is a city that has a fairly wide coastline and has a high level of disaster risk because it is a city. pariaman is located on the coast. This type of research is qualitative research using descriptive methods. Data collection techniques are carried out by means of interviews, observation and documentation studies, research instruments, namely the author himself, which the authors use, namely the interview guidelines that the author has prepared, the tools used in collecting data are cameras, cellphones, and voice recorders. For data collection using source triangulation. The results showed that there are several obstacles in mangrove conservation activities as a means of disaster risk reduction in Kota Pariaman, namely internal constraints, namely a lack of budget, lack of cooperation between the government and stakeholders who are both engaged in mangrove conservation, the external constraints are lack of public knowledge of the importance of mangrove forests for disaster risk reduction.